(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Skin cancer is the most common malignancy worldwide, including malignant melanoma and Non-malignant melanoma. The progressive increase in the incidence of skin cancers is observed, mainly in cutaneous melanomas over the last few decades. UV exposure is the most common cause of skin cancer, which occurs due to mutations in the DNA of skin cells. The mutation in MAPK pathway was the main cause of the skin cancer, in which BRAF gene undergoes 75 somatic mutations. The mutation in DNA suppressed the tumor suppressor gene p53, inactivates DNA repair gene and causes mutation in proto-oncogene results in the formation of oncogene which promote the cell growth, cell proliferation and cell reproduction by affecting the process of apoptosis. Skin cancer can be prevented by healthy dietary intervention and regular physical activity. In the current review, we highlight recent global trends in the treatments of skin cancer which involve chemotherapy, radiotherapy, photodynamic therapy, biological therapy and surgery. These therapies show the effectiveness by improving the survival rate and quality of life.